Does high fat diet effect the bone-implant connection? - Dundar, S.; Bozoglan, A.; Şahin, Kazım; Balci, T. A.; Kirtay, M.; Bozoglan, M. Y.; Calisir, M. (Comenius Univ, 2020)
OBJECTIVE: Obesity induced by a high fat diet is associated with chronic up-regulation of inflammatory cytokines which stimulate osteoclast activity and bone resorption. However, the role of high-fat diet on bone-implant connectivity has not been studied in detail. In this study, we investigated whether a high-fat diet (HFD) affects bone implant connection (BIC) in periimplant bone. METHODS: Twenty female Sprague Dawley rats were divided in two groups: 1) Control rats were fed with normal chow and titanium implants were integrated into tibial bones at the end of 3rd month and no treatment was applied 2) HFD group; rats were fed a high-fat diet (42 % of calories as fat), then the titanium implants were integrated into tibial bones at the end 3rd month. Following surgical integration of the implants, the rats were fed with control and HFD diets for 3 months. After the 6 months experimental period all rats were sacrificed and the implants and surrounded bone tissues were collected and the BIC was assessed histomorphometrically after the non-decalcifiing histological methods. Bone implant connection was detected with the ratio of the implant surface directly connected with the peri-implant bone tissues to the total implant surface length. RESULTS: Histologic analysis showed that HFD was not impaired BIC (p> 0.05). CONCLUSION: In conclusion, within the limitation of this research, HFD did not effect the BIC rat tibias (Tab. 2, Fig. 2, Ref. 26). Text in PDF www.elis.sk.
Keywords: bone-implant contact; osseointegration; dental implants; high fat diet